HUBUNGAN TINGKAT PENGETAHUAN BAHAYA ROKOK DAN HUKUM MEROKOK DALAM ISLAM TERHADAP PERILAKU MEROKOK PADA GENERASI Z DI KELURAHAN SUKATANI RW 008, KABUPATEN TANGERANG - musrifatunupus nupus (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Smoking behavior in Indonesia is still tolerated by the community, this can be seen from everyday life, and based on data (Indonesian Youth Statistics, 2024), around 23.08% of youth in Indonesia are identified as active smokers with an average consumption of 12 cigarettes a day, to determine the relationship between the level of knowledge of the dangers of cigarettes and the law of smoking in Islam on smoking behavior in Generation Z in Sukatani Village RW 008, Tangerang Regency, The method used is a quantitative method and the type of correlational analysis research with a cross-sectional approach. The sampling technique with non-probability sampling uses purposive sampling. The population of 176 Gen Z who smoke with a sample of 122 respondents. The results of data analysis show a relationship between the level of knowledge of the dangers of cigarettes on smoking behavior, with a p-value of 0.000. And the relationship between the level of knowledge of the law of smoking in Islam on smoking behavior, with a p-value of 0.000. Keywords: Knowledge, Dangers of Cigarettes, Islamic Law, Smoking Behavior, Generation Z